Exploring the Link Between Innovation Culture and Organizational Performance: A Study of Select IT Companies - Manzoor, Mehnaz; Dhand, Shivani; Pandey, Aayushi (Journal of Neonatal Surgery, 2025)
Innovation culture plays a crucial role in shaping the competitive advantage and sustainability of IT companies in a rapidly evolving business landscape. This study explores the relationship between innovation culture and organizational performance in select IT firms, emphasizing how a conducive environment for creativity, knowledge sharing, and risk-taking fosters business growth. Using Structural Equation Modeling (SEM), the study examines the impact of innovation culture on organizational performance, considering mediating factors such as leadership support and employee engagement. Data was collected through a structured questionnaire from IT employees across different hierarchical levels in selected firms. The findings reveal that organizations with a strong innovation culture exhibit higher productivity, efficiency, and market adaptability. Furthermore, leadership commitment and employee empowerment significantly mediate this relationship. The study also highlights the challenges that hinder innovation, such as resistance to change and rigid organizational structures. The implications for managers and policymakers emphasize the need for a structured innovation strategy aligned with corporate objectives. This research contributes to the existing literature by providing empirical evidence on the critical role of innovation culture in enhancing organizational performance. It offers strategic recommendations for IT firms to foster an environment that nurtures continuous improvement, collaboration, and technological advancement. The study concludes that fostering an innovation-driven culture is essential for achieving long-term sustainability in the digital era